The Routledge companion to international human resource management edited by David G. Collings, Geoffrey T. Wood and Paula M. Caligiuri - Collings, David G.; Wood, Geoffrey T.; Caligiuri, Paula M. (Routledge, 2015)
International human resource management (IHRM) is a key area of research in the sphere of international business and management. Described as a field in its infancy in the 1980s, IHRM has quickly advanced through adolescence and into maturity. Today, it is a vibrant and diverse discipline which boasts a large and active body of researchers across the globe. This volume examines cutting-edge themes, with the input of contributions from both established and emerging scholars. The Routledge Companion to International Human Resource Management gives a state-of-the-art overview of the key themes, topics and debates in the discipline, with valuable insights into directions for future research. Drawing on a large and respected international contributor base and with its focus on mature and emerging markets, this book is an essential resource for researchers, students and IHRM professionals alike
Keywords: International business enterprises -- Personnel management; Personnel management -- Cross-cultural studies; Humanvermögen; Personalentwicklung; Internationales Management; Aufsatzsammlung